2020
DOI: 10.1128/aem.00441-20
|View full text |Cite
|
Sign up to set email alerts
|

The Sterol Carrier Hydroxypropyl-β-Cyclodextrin Enhances the Metabolism of Phytosterols by Mycobacterium neoaurum

Abstract: Androst-4-ene-3,17-dione (AD) and androst-1,4-diene-3,17-dione (ADD) are valuable steroid pharmaceutical intermediates obtained by soybean phytosterol biotransformation by Mycobacterium. Cyclodextrins (CDs) are generally believed to be carriers for phytosterol delivery and can improve the production of AD and ADD due to their effects on steroid solubilization and alteration in cell wall permeability for steroids. To better understand the mechanisms of CD promotion, we performed proteomic quantification of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 54 publications
1
21
0
Order By: Relevance
“…However, the purity of 9-OH-4-HP remained stable. Previous research has reported that phytosterols and their metabolites could be noxious to cells during bioconversion [ 9 , 14 16 ], for the poor performance of Δ kstD Δ hsd4A Δ fadA5 under high concentration phytosterols bioconversion.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the purity of 9-OH-4-HP remained stable. Previous research has reported that phytosterols and their metabolites could be noxious to cells during bioconversion [ 9 , 14 16 ], for the poor performance of Δ kstD Δ hsd4A Δ fadA5 under high concentration phytosterols bioconversion.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Some surfactants like Tween 80 can reduce the tendency of Mycobacterium to aggregate [ 25 ] and thus promote the formation of stable suspensions of phytosterol by increasing phytosterol solubility and decreasing dynamic interfacial tension [ 23 ].These above cause the improvement of phytosterol bioconversion. Sterol-solubilizing agents like cyclodextrins could form inclusion complexes with steroids and make them as the effective carriers to deliver of hydrophobic steroids to cells, which enhances the biotransformation of steroid compounds [ 26 ]. Phytosterols and their derivatives are also reported to be toxic and inhibitory to cell growth [ 26 , 27 ], which also hinder the bioconversion and result in low molar yields.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yao et al reported an engineered Mycobacterium-transformed PS to 9a-OH-AD. 5 In addition, diverse sterol-solubilizing reaction systems, including a cyclodextrin complexing system, 4,6 biocompatible ionic liquid system, 7 microdispersion/emulsication system, and surfactant addition, 8,9 were established to improve the poor water solubility of PS. Among them, the cyclodextrin-resting cell system is an ideal method that has been successfully used for the production of a variety of steroid intermediates.…”
Section: Introductionmentioning
confidence: 99%